1987
DOI: 10.1111/j.1525-1314.1987.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability relations of Mn–Fe–Al piemontite

Abstract: Comparison of the stability relations of Fe-piemontite, Pm,,Ps,,Cz, (Ca2A12Mnl).S Fe,,,sSi30 I 2( OH)), with similar experimentally determined results on P~,,CZ,,~ suggests that, at moderate fo,, addition of Fe to piemontite raises its thermal stability and slightly decreases its sensitivity to oxygen fugacity. Reversal study of the reaction:Fe-piemontite + quartz = garnet at Pffuid = 2 kbar in cold-seal apparatus using solid oxygen buffers was completed. The data indicated breakdown of Pm17Ps17Czhtr at 645" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
(34 reference statements)
1
14
0
2
Order By: Relevance
“…Because epidote minerals occur in shallow geothermal fields at depth of only a few hundred meters, such epidotes may have crystallized at pressures of less than 100 MPa and temperatures below 200 °C (Bird and Spieler, 2004). As noted above, several experimental studies of the stability of epidote minerals (Holdaway, 1966(Holdaway, , 1972Liou, 1973;Keskinen and Liou, 1987) have confirmed that epidote minerals are stable at low pressures of 100 200 MPa, which is consistent with the natural occurrences of epidote minerals. However, the experimental results of epidote synthesis are not necessarily compatible with those on epidote stability, because Cz Ps series epidotes have never been crystallized as single phases by syntheses at low pressures less than 400 MPa.…”
Section: Implication To Natural Epidote and Piemontitesupporting
confidence: 51%
See 2 more Smart Citations
“…Because epidote minerals occur in shallow geothermal fields at depth of only a few hundred meters, such epidotes may have crystallized at pressures of less than 100 MPa and temperatures below 200 °C (Bird and Spieler, 2004). As noted above, several experimental studies of the stability of epidote minerals (Holdaway, 1966(Holdaway, , 1972Liou, 1973;Keskinen and Liou, 1987) have confirmed that epidote minerals are stable at low pressures of 100 200 MPa, which is consistent with the natural occurrences of epidote minerals. However, the experimental results of epidote synthesis are not necessarily compatible with those on epidote stability, because Cz Ps series epidotes have never been crystallized as single phases by syntheses at low pressures less than 400 MPa.…”
Section: Implication To Natural Epidote and Piemontitesupporting
confidence: 51%
“…The role of Fe 3+ in epidote group minerals has been recognized from two aspects: (1) incorporation of Fe 3+ in epidote group minerals expands their stability range toward both high and low temperatures (Holdaway, 1966(Holdaway, , 1972Liou, 1973;Keskinen and Liou, 1987); (2) f O 2 values in excess of those defined by the QFM buffer curve causes considerable expansion of the stability range of epidotes (Holdaway, 1972;Liou, 1973). Fe 3+ in epidote group minerals affects on not only the stability temperatures but also stability pressures, because the stability fields of epidote, clinozoisite and zoisite are located in their order with increasing pressure (Holdaway, 1972) and, thus, epidote is stable at lower pressures than Fe 3+ free clinozoisite and zoisite.…”
Section: Role Of Fe 3+ and Mn 3+ In Crystallization Of Epidote Group mentioning
confidence: 99%
See 1 more Smart Citation
“…The former are well-known to represent higher oxidation conditions than the latter (Smith and Albee, 1967;Kawachi et al, 1983). The experimental data of Keskinen and Liou (1979) and Anastasiou and Langer (1977) imply f(0 2 ) higher than 10~2 0 -10" 10 for piemontite with 33 mol% Pm. Thus, an even higher f(0 2 ) must be assumed for the stabilization of Pm-rich piemontites such as those occurring at St. Marcel.…”
Section: Determination Of F(02)mentioning
confidence: 88%
“…The aims of the present investigations are therefore the following: a) to review the existing data on sedimentary and metamorphic cherts related to ophiolites in the Alpine belt, in order to establish their peculiar geochemical characteristics, the extent of the chemical transformation undergone during the subduction metamorphism, and to identify the elements suitable to act as geochemical tracers for other outcrops where no evidence of oceanic vs. continental derivation survived the blueschist-facies metamorphism; b) to review the mineralogy and phase petrology so as to help clarify the application of experimental studies in the synthetic Mn-Si-Ca-C-O-H system currently underway (Abs-Wurmbach and Abs-Wurmbach, 1980;Maresch and Mottana, 1976;Keskinen and Liou, 1979;Peters et al, 1973;. This will eventually widen the use of rocks easily recognizable in the field from the mere condition of structural markers to that of indicators of equilibration within the high-pressurefacies sequence.…”
Section: Introductionmentioning
confidence: 99%